Expedient preparative isolation and tandem mass spectrometric characterization of C-seco triterpenoids from neem oil - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Dandekar, Devdutta S.; Thulasiram, Hirekodathakallu V. (Journal of Chromatography A, 2014)
C-seco triterpenoids are widely bioactive class of natural products with high structural complexity and diversity. The preparative isolation of these molecules with high purity is greatly desirable, although restricted due to the complexity of natural extracts. In this article we have demonstrated a Medium Pressure Liquid Chromatography (MPLC) based protocol for the isolation of eight major C-seco triterpenoids of salannin skeleton from Neem (Azadirachta indica) oil. Successive application of normal phase pre-packed silica-gel columns for the fractionation followed by reverse phase in automated MPLC system expedited the process and furnished highly pure metabolites. Furthermore, eight isolated triterpenoids along with five semi-synthesized derivatives were characterized using ultra performance liquid chromatography-electrospray ionization-quadrupole/orbitrap-MS/MS spectrometry as a rapid and sensitive identification technique. The structure-fragment relationships were established on the basis of plausible mechanistic pathway for the generation of daughter ions. The MS/MS spectral information of the triterpenoids was further utilized for the identification of studied molecules in the complex extract of stem and bark tissues from Neem. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ESI(+)-quadrupole/orbitrap-MS/MS; MPLC; Neem oil; Preparative isolation; Salannin; Triterpenoids

Triterpenoid profiling and functional characterization of the initial genes involved in isoprenoid biosynthesis in neem (Azadirachta indica) - Pandreka, Avinash; Dandekar, Devdutta S.; Haldar, Saikat; Uttara, Vairagkar; Vijayshree, Shinde G.; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2015)
Background: Neem tree (Azadirachta indica) is one of the richest sources of skeletally diverse triterpenoids and they are well-known for their broad-spectrum pharmacological and insecticidal properties. However, the abundance of Neem triterpenoids varies among the tissues. Here, we delineate quantitative profiling of fifteen major triterpenoids across various tissues including developmental stages of kernel and pericarp, flower, leaf, stem and bark using UPLC-ESI (+)-HRMS based profiling. Transcriptome analysis was used to identify the initial genes involved in isoprenoid biosynthesis. Based on transcriptome analysis, two short-chain prenyltransferases and squalene synthase (AiSQS) were cloned and functionally characterized. Results: Quantitative profiling revealed differential abundance of both total and individual triterpenoid content across various tissues. RNA from tissues with high triterpenoid content (fruit, flower and leaf) were pooled to generate 79.08 million paired-end reads using Illumina GA.. platform. 41,140 transcripts were generated by d e novo assembly. Transcriptome annotation led to the identification of the putative genes involved in isoprenoid biosynthesis. Two short-chain prenyltransferases, geranyl diphosphate synthase (AiGDS) and farnesyl diphosphate synthase (AiFDS) and squalene synthase (AiSQS) were cloned and functionally characterized using transcriptome data. RT-PCR studies indicated five-fold and ten-fold higher relative expression level of AiSQS in fruits as compared to leaves and flowers, respectively. Conclusions: Triterpenoid profiling indicated that there is tissue specific variation in their abundance. The mature seed kernel and initial stages of pericarp were found to contain the highest amount of limonoids. Furthermore, a wide diversity of triterpenoids, especially C-seco triterpenoids were observed in kernel as compared to the other tissues. Pericarp, flower and leaf contained mainly ring-intact triterpenoids. The initial genes such as AiGDS, AiFDS and AiSQS involved in the isoprenoids biosynthesis have been functionally characterized. The expression levels of AiFDS and AiSQS were found to be in correlation with the total triterpenoid content in individual tissues.
Keywords: Azadirachta indica; Quantitative profiling; Transcriptome; Triterpenoids

Whole-cell mediated 11 beta-hydroxylation on the basic limonoid skeleton by cunninghamella echinulata - Haldar, Saikat; Mulani, Fayaj A.; Aarthy, Thiagarayaselvam; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2015)
Regio- and stereoselective 11 beta-hydroxylation was achieved on the basic limonoid skeleton through microbial transformation. Whole cells of Cunninghamella echinulata efficiently converted basic limonoids such as epoxyazadiradione, azadiradione, and gedunin to their 11 beta-hydroxy analogues as the sole metabolite. Fermentation conditions affecting the efficiency (96%) of biotransformation including substrate concentration, incubation period, pH, and temperature were optimized. The position and stereochemistry of hydroxyl functionality on the isolated metabolites were established through extensive spectroscopic and spectrometric studies (1D, 2D NMR, ESI-MS, and MS/MS).

Tracing the biosynthetic origin of limonoids and their functional groups through stable isotope labeling and inhibition in neem tree (Azadirachta indica) cell suspension - Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Pandreka, Avinash; Kumar, Ashish; Nandikol, Sharvani S.; Haldar, Saikat; Thulasiram, Hirekodathakallu V. (BMC Plant Biology, 2018)
Background Neem tree serves as a cornucopia for triterpenoids called limonoids that are of profound interest to humans due to their diverse biological activities. However, the biosynthetic pathway that plant employs for the production of limonoids remains unexplored for this wonder tree. Results Herein, we report the tracing of limonoid biosynthetic pathway through feeding experiments using C-13 isotopologues of glucose in neem cell suspension. Growth and development specific limonoid spectrum of neem seedling and time dependent limonoid biosynthetic characteristics of cell lines were established. Further to understand the role of mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways in limonoid biosynthesis, Ultra Performance Liquid Chromatography (UPLC)- tandem mass spectrometry based structure-fragment relationship developed for limonoids and their isotopologues have been utilized. Analyses of labeled limonoid extract lead to the identification of signature isoprenoid units involved in azadirachtin and other limonoid biosynthesis, which are found to be formed through mevalonate pathway. This was further confirmed by treatment of cell suspension with mevinolin, a specific inhibitor for MVA pathway, which resulted in drastic decrease in limonoid levels whereas their biosynthesis was unaffected with fosmidomycin mediated plastidial methylerythritol 4-phosphate (MEP) pathway inhibition. This was also conspicuous, as the expression level of genes encoding for the rate-limiting enzyme of MVA pathway, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) was comparatively higher to that of deoxyxylulose-phosphate synthase (DXS) of MEP pathway in different tissues and also in the in vitro grown cells. Thus, this study will give a comprehensive understanding of limonoid biosynthetic pathway with differential contribution of MVA and MEP pathways. Conclusions Limonoid biosynthesis of neem tree and cell lines have been unraveled through comparative quantification of limonoids with that of neem tree and through C-13 limonoid isotopologues analysis. The undifferentiated cell lines of neem suspension produced a spectrum of C-seco limonoids, similar to parental tissue, kernel. Azadirachtin, a C-seco limonoid is produced in young tender leaves of plant whereas in the hard mature leaves of tree, ring intact limonoid nimocinol accumulates in high level. Furthermore, mevalonate pathway exclusively contributes for isoprene units of limonoids as evidenced through stable isotope labeling and no complementation of MEP pathway was observed with mevalonate pathway dysfunction, using chemical inhibitors.

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis (vol 184, 112669, 2021) - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, Hirekodathakallu V. (Phytochemistry, 2021)

Limonoid biosynthesis 3: functional characterization of crucial genes involved in neem limonoid biosynthesis - Pandreka, Avinash; Chaya, Patil S.; Kumar, Ashish; Aarthy, Thiagarayaselvam; Mulani, Fayaj A.; Bhagyashree, Date D.; Shilpashree, H. B.; Jennifer, Cheruvathur; Ponnusamy, Sudha; Nagegowda, Dinesh; Thulasiram, V. Hirekodathakallu (Phytochemistry, 2021)
Neem (Azadirachta indica L.) is well known for its medicinal, agricultural, and pesticidal applications since ages. The secondary metabolites, limonoids, confer these biological properties, wherein over 150 different limonoids have been reported from neem. To understand limonoid biosynthesis, we analyzed tissue-specific (kernel, pericarp, leaves, and flower) transcriptome that resulted in the identification of one farnesyl diphosphate synthase (AiFDS), one squalene synthase (AiSQS), three squalene epoxidases (AiSQE1, AiSQE2, and AiSQE3), two triterpene synthases (AiTTS1 and AiTTS2), cycloartenol synthase (AiCAS), two cytochrome P450 reductases, and ten cytochrome P450 systems. Comparative tissue-expression analysis indicated that AiFDS, AiSQS, AiSQE3, and AiTTS1 are expressed higher in the kernel than in the other tissues. Heterologously expressed recombinant AiTTS1 produced tirucalla-7,24-dien-3 beta-ol as the sole product. Expression profile data, phylogeny with triterpene synthases from Meliaceae and Rutaceae families, real-time PCR of different tissues, and transient transformation revealed the involvement of tirucalla-7,24-dien-3 beta-ol synthase (AiTTS1) in limonoid biosynthesis. Further, mutagenesis studies of AiTTS1 indicated that Y125 and F260 are probably involved in stabilization of dammarenyl cation. A 2.6-fold increase in production of tirucalla-7,24-dien-3 beta-ol was observed when AiSQE1 was coexpressed with mutant AiTTS1 in a yeast system. Furthermore, we functionally characterized the highly expressed cytochrome P450 reductases and cycloartenol synthase. This study helps in further analysis and identification of genes involved in limonoid biosynthesis in Meliaceae/Rutaceae and their production in a metabolically tractable heterologous system.
Keywords: 24-dien-3 beta-ol; Azadirachta indica A. Juss.; Cytochrome P450 system; Limonoids; Meliaceae; Tirucalla-7; Transcriptome

Stacking herbicide detoxification and resistant genes improves glyphosate tolerance and reduces phytotoxicity in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.) - Vennapusa, Amaranatha Reddy; Agarwal, Subham; Hm, Hanumanth Rao; Aarthy, Thiagarayaselvam; Babitha, K. C.; Thulasiram, V. Hirekodathakallu; Kulkarni, Mahesh J.; Melmaiee, Kalpalatha; Sudhakar, Chinta; Udayakumar, M.; Vemanna, Ramu S. (Plant Physiology and Biochemistry, 2022)
Glyphosate residues retained in the growing meristematic tissues or in grains of glyphosate-resistant crops affect the plants physiological functions and crop yield. Removing glyphosate residues in the plants is desirable with no penalty on crop yield and quality. We report a new combination of scientific strategy to detoxify glyphosate that reduces the residual levels and improve crop resistance. The glyphosate detoxifying enzymes Aldo-keto reductase (AKR1) and mutated glycine oxidase (mGO) with different modes of action were co-expressed with modified EPSPS, which is insensitive to glyphosate in tobacco (Nicotiana tabacum L.) and rice (Oryza sativa L.). The transgenic tobacco plants expressing individual PsAKR1, mGO, CP4-EPSPS, combinations of PsAKR1:CP4EPSPS, PsAKR1:mGO, and multigene with PsAKR1: mGO: CP4EPSPS genes were developed. The bio-efficacy studies of in-vitro leaf regeneration on different concentrations of glyphosate, seedling bioassay, and spray on transgenic tobacco plants demonstrate that glyphosate detoxification with enhanced resistance. Comparative analysis of the transgenic tobacco plants reveals that double and multigene expressing transgenics had reduced accumulation of shikimic acid, glyphosate, and its primary residue AMPA, and increased levels of sarcosine were observed in all PsAKR1 expressing transgenics. The multigene expressing rice transgenics showed improved glyphosate resis-tance with yield maintenance. In summary, results suggest that stacking genes with two different detoxification mechanisms and insensitive EPSPS is a potential approach for developing glyphosate-resistant plants with less residual content.
Keywords: Detoxification; Gene stacking; Glyphosate; Herbicide; Multigene; Residual toxicity; Resistant; rice; Tobacco; Transgenics